2013
DOI: 10.1074/jbc.m113.498337
|View full text |Cite
|
Sign up to set email alerts
|

The Extracellular Chaperone Haptoglobin Prevents Serum Fatty Acid-promoted Amyloid Fibril Formation of β2-Microglobulin, Resistance to Lysosomal Degradation, and Cytotoxicity

Abstract: Background:The role of chaperones in extracellular space is important. Haptoglobin, an extracellular chaperone, is investigated in the context of ␤ 2 -microglobulin amyloidosis. Results: Haptoglobin interacts with prefibrillar species, facilitates intracellular degradation, and prevents formation of cytotoxic ␤2m fibrils. It exhibits pH-dependent chaperone activity. Conclusions: Haptoglobin is an extracellular chaperone for ␤ 2 -microglobulin under normal and inflammation-induced acidosis conditions. Significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 50 publications
1
13
0
1
Order By: Relevance
“…Similar results have been previously shown for chaperones [34][35][36], some non-chaperone proteins such as pyruvate kinase and seeds. Particles with all dimensions smaller than 30 nm were defined as oligomers while particles with any dimension over 30 nm were defined as fibrils catalase [37] and some small molecules [28].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results have been previously shown for chaperones [34][35][36], some non-chaperone proteins such as pyruvate kinase and seeds. Particles with all dimensions smaller than 30 nm were defined as oligomers while particles with any dimension over 30 nm were defined as fibrils catalase [37] and some small molecules [28].…”
Section: Discussionsupporting
confidence: 90%
“…Particles with all dimensions smaller than 30 nm were defined as oligomers while particles with any dimension over 30 nm were defined as fibrils catalase [37] and some small molecules [28]. Both chaperone and non-chaperone proteins that inhibited protein aggregation were shown to bind to target proteins [34,35,37,36].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the effects of chaperones (3941), metal ions (19, 32, 42), membranes (43), trifluoroethanol or SDS co-solvents (28, 29, 44), GAGs (18, 30, 45, 46), and other natural compounds (13, 17, 47) on the formation of amyloid fibrils in vitro . For some of these compounds, detailed kinetic analysis has revealed the effect of each reagent on the different kinetic steps in aggregation, including primary nucleation, elongation from fibril ends, and secondary processes such as fibril fragmentation and secondary nucleation (3941, 43, 48). Such studies can provide important information on the role of biologically relevant and other compounds on amyloid formation, including how the different factors may act synergistically to alter the course of aggregation in an in vitro setting (17, 30).…”
Section: Discussionmentioning
confidence: 99%
“…Motomiya et al reported that b2M fragments having C-terminal unfolding, including a fragment lacking the first 6 amino acids (DN6b2M), 13 which has been recognized as an important amyloidogenic form, are essential for amyloidogenesis. 14 15 Naiki et al, 16,17 and other researchers 18…”
Section: Of B 2m and Amyloid Fibr Il Formationmentioning
confidence: 95%
“…Hereditary systemic amyloidosis due to the Asp76Asn‐β2M variant—a new type of Aβ2M with normal renal function—also suggests the importance of conformational change for β2M amyloidogenesis . Naiki et al, and other researchers identified numerous promoters (ie, type 1,2 collagen, glycosaminoglycan including heparin, proteoglycan, apolipoprotein E, lysophospholipid, free fatty acids, and pentraxins (serum amyloid P component and C‐reactive protein), and inhibitors (ie, α2 macroglobulin and haptoglobin)) of Aβ2M formation and elongation in in vitro studies.…”
Section: Pathogenesis Of Dra: Retention Of β2m and Amyloid Fibril Formentioning
confidence: 99%